A two-phase model to simulate the 1-D shock wave propagation in porous metal foam. (August 2015) - Feldgun, V.R.; Karinski, Y.S.; Yankelevsky, D.Z.
Abstract: A two-phase model is proposed to simulate the dynamic behavior of porous metal foam. The model is applied to known experimental data describing equations of state for different aluminum foams. To analyze impact and shock problems in compressible media with analytical, semi-analytical and numerical methods, the corresponding Riemann problem solution is required. Its solution for a metal foam medium has been obtained. The possible wave configurations have been analyzed and the corresponding equations for the contact pressure and velocity evaluation have been derived. The effect of the volumetric air content in a metal foam medium on the Riemann problem solution has been investigated. The proposed equation of state has been successfully used to simulate shock waves propagation in the Alporas foam. The comparisons of the present model predictions with numerical results computed with LS-Dyna as well as with experimental data show very good correspondence and demonstrate the power of the present approach. Graphical abstract: Highlights: The model of two-phase porous medium has been proposed to simulation of dynamic behavior of metal foams. The Riemann problem for the metal foam medium has been solved. The proposed approach is demonstrated by comparison with experimental data. The effect of the air volumetric content in a metal foam on the Riemann problem solution has been investigated.